Biodegradable Polymer/TiO2 Nanotubes Loaded Roxithromycin as Nanoarray Capsules for Long-Lasting Antibacterial Properties of Titanium Implant. (28th December 2020) - Ouyang, Jianglin; Huang, Haochao; Chen, Xianshuai; Chen, Jianyu
Abstract : Bacterial infection is one of the main reasons for the clinical failure of oral titanium restorations. In this study, biodegradable polymer/TiO2 nanotube nanoarray capsules were constructed on a titanium substrate surface to locally deliver drugs for long-lasting antibacterial properties. Anodization was applied to prepreparation TiO2 nanotube array film on titanium substrate, and then, the upward opening TiO2 nanotubes were sealed with biodegradable polymer (chitosan and polyethylene glycol) through electrochemical deposition. Scanning electron microscope (SEM) and X-ray photoelectron spectroscopy (XPS) were used to analyze the characterization of this system. The drug release characteristics and the antibacterial activity demonstrated that the polymer coating significantly reduced burst release and enhanced lasting antibacterial properties. The nanoarray capsules still preserved integrity with a little degradation after 2 days. The strategy described herein provides a versatile route for designing targeted drug delivery systems in orthopaedical and other biomedical fields.